2000
DOI: 10.1096/fasebj.14.7.885
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial K+channel lacks the Ca2+sensitivity‐regulating β subunit

Abstract: Hyperpolarizing large-conductance, Ca(2+)-activated K(+) channels (BK) are important modulators of vascular smooth muscle and endothelial cell function. In vascular smooth muscle cells, BK are composed of pore-forming alpha subunits and modulatory beta subunits. However, expression, composition, and function of BK subunits in endothelium have not been studied so far. In patch-clamp experiments we identified BK (283 pS) in intact endothelium of porcine aortic tissue slices. The BK opener DHS-I (0.05-0.3 micromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
44
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 38 publications
4
44
0
Order By: Relevance
“…However, when expressed in freshly isolated or cultured endothelial cells, BK Ca channels that are characterized by calcium and voltage dependence, iberiotoxin sensitivity, and a conductance between 190 and 300 pS are detected (6,17,26,28). Interestingly, the properties of the BK Ca channel in the human endothelial cell line EA.hy926 (26) are similar to those of the mitoBK Ca channel described in this study. The BK Ca channel of EA.hy926 cells has a single-channel conductance of 270 pS, which is the same as that of its mitoBK Ca channel counterpart.…”
supporting
confidence: 76%
See 3 more Smart Citations
“…However, when expressed in freshly isolated or cultured endothelial cells, BK Ca channels that are characterized by calcium and voltage dependence, iberiotoxin sensitivity, and a conductance between 190 and 300 pS are detected (6,17,26,28). Interestingly, the properties of the BK Ca channel in the human endothelial cell line EA.hy926 (26) are similar to those of the mitoBK Ca channel described in this study. The BK Ca channel of EA.hy926 cells has a single-channel conductance of 270 pS, which is the same as that of its mitoBK Ca channel counterpart.…”
supporting
confidence: 76%
“…In some freshly isolated endothelial cells, BK Ca channels are poorly expressed and iberiotoxin-sensitive currents are observed only at very positive potentials (15). This has been attributed to the absence of BK Ca regulatory ␤-subunits that increase the sensitivity to Ca 2ϩ in these cells (26). However, when expressed in freshly isolated or cultured endothelial cells, BK Ca channels that are characterized by calcium and voltage dependence, iberiotoxin sensitivity, and a conductance between 190 and 300 pS are detected (6,17,26,28).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The main K + channels expressed in resistance vessels, from a functional point of view, are: the ATP-sensitive K + channels (K ATP ), inward rectifying K + channels (K ir ) and Ca 2+ -activated K + channels (K Ca ) of small (SK Ca ), intermediate (IK Ca ) and large (BK Ca ) conductance (Jackson, 2000(Jackson, , 2005. K ATP and K ir are expressed in both endothelial and smooth muscle cells (Quayle et al, 1996;Jackson, 2000Jackson, , 2005Ko et al, 2008), whereas BK Ca are mostly found in smooth muscle cells (Jackson, 2005;Ko et al, 2008), but, on occasion, these K + channels have also been described in endothelial cells (Papassotiriou et al, 2000;Wang et al, 2005). In contrast, SK Ca and IK Ca are expressed exclusively in endothelial cells (Jackson, 2000;Kohler et al, 2000;Nilius & Droogmans, 2001;Eichler et al, 2003;Taylor et al, 2003;Brahler et al, 2009).…”
Section: Membrane Potential and Vascular K + Channelsmentioning
confidence: 99%